Incentives for wind power investment in Colombia (2016)
This paper develops an energy policy measure for renewable sources in Colombia, in particular wind generation. The proposal is done at the decentralized level, in isolated areas of the country, where electricity coverage is below 12% and wind speed is suitable for power generation. The goal of this policy is focused on increasing electricity coverage in those remote areas of the country that have high winds in order to develop clean generation investments that can represent a benefit for low-income users. Thus, a mechanism for financing these kinds of investments is proposed, involving the private sector and using the mechanism known as Public Private Partnerships - PPPs. PPPs are mechanisms used by the public sector to establish a contract with the private sector. The private sector provides capital and ability to develop projects, while the public sector holds the responsibility in service delivery. To model the relationship between public sector and private investors, a bilevel programming method for efficient resource allocation, combining an auction mechanism and moral hazard, is presented. A case study is shown in the Colombian context. © 2015 Elsevier Ltd.